Informal community support for parents of pre-school children: A comparative study investigating the subjective experience of parents attending community-based toddler groups in different socio-economic situations. (June 2017) - Owen, Alex; Anderson, Babs
Within the United Kingdom, the importance of the appropriate parenting of children in their early years has received significant political support. However, it has been found that positive outcomes for young children, in terms of their present experience and future life chances, are often significantly weakened by the impact of poverty. A phenomenological scoping study was undertaken to explore the reasons why parents living in poverty access informal social support networks, in the form of community-based toddler groups. The study found that engagement with these networks has value for parents in terms of their mental well-being and their peer education, both of which support their ability to parent a young child appropriately.